RANCANG BANGUN WEBSITE SEBAGAI MEDIA INFORMASI DAN PENJUALAN PRODUK MENGGUNAKAN FRAMEWORK LARAVEL - Muhammad Rafi (Universitas Lampung, 2026)
The rapid development of information technology encourages companies to provide accessible and professional digital media for presenting their identity and services. CV. Saira Teknik requires a web-based platform that not only delivers comprehensive company profile information but also enables customers to place product orders online. To address this need, this research designs and develops a company profile website integrated with an online ordering feature using the Laravel framework. The development process follows the Agile Scrum methodology through stages of requirement analysis, system design, backlog preparation, iterative development, and testing. The system includes features for managing company information, categories, products, customer orders, and sales reports for administrators, while customers can view company information, browse products, manage their carts, and perform transactions. The system is evaluated using alpha testing with the black box method and beta testing through User Acceptance Testing (UAT). The results show that all functionalities operate as expected, with UAT feasibility scores of 86% from administrators and 92% from customers, categorized as very good. Therefore, the developed website is considered feasible and effective in improving information delivery and the ordering process at CV. Saira Teknik.